упростите выражение 1/a+1 -a/a^2-1 : a/(a-1)^2 -3a+6/a+1

0 голосов
28 просмотров

упростите выражение 1/a+1 -a/a^2-1 : a/(a-1)^2 -3a+6/a+1


Алгебра (19 баллов) | 28 просмотров
Дано ответов: 2
0 голосов

У меня получилось -4, хотя не знаю правильно ли это.

(20 баллов)
0 голосов

(1/a+1) - (a/(a-1)(a+1)) : (a/(a-1)^2) - (3a+6)/(a+1)

(1/a+1) - (a/(a-1)(a+1)) * ((a-1)^2/ a) - (3a+6)/(a+1)

 сокращается =

(1/a+1) - (a-1)/(a+1) - (3a+6)/(a+1)

(1-a+1-3a-6)/(a+1) =(-4-4a)/(a+1)=(-4(1+a))/(a+1)

сокращается =-4

(14 баллов)